3D‐Printed Gastric Resident Electronics. Issue 3 (13th December 2018) - Kong, Yong Lin; Zou, Xingyu; McCandler, Caitlin A.; Kirtane, Ameya R.; Ning, Shen; Zhou, Jianlin; Abid, Abubakar; Jafari, Mousa; Rogner, Jaimie; Minahan, Daniel; Collins, Joy E.; McDonnell, Shane; et al.
Abstract: Long‐term implantation of biomedical electronics into the human body enables advanced diagnostic and therapeutic functionalities. However, most long‐term resident electronics devices require invasive procedures for implantation as well as a specialized receiver for communication. Here, a gastric resident electronic (GRE) system that leverages the anatomical space offered by the gastric environment to enable residence of an orally delivered platform of such devices within the human body is presented. The GRE is capable of directly interfacing with portable consumer personal electronics through Bluetooth, a widely adopted wireless protocol. In contrast to the passive day‐long gastric residence achieved with prior ingestible electronics, advancement in multimaterial prototyping enables the GRE to reside in the hostile gastric environment for a maximum of 36 d and maintain ≈15 d of wireless electronics communications as evidenced by the studies in a porcine model. Indeed, the synergistic integration of reconfigurable gastric‐residence structure, drug release modules, and wireless electronics could ultimately enable the next‐generation remote diagnostic and automated therapeutic strategies. Abstract : 3D‐printed orally delivered gastric resident electronic devices allow a needle and surgical‐free synergistic integration of biomedical electronics, the human body, and the digital domain. A maximum gastric residence of 36 and 15.3 d of wireless Bluetooth communication is demonstrated in a hostile gastric environment, enabling the next‐generation remote diagnostic and automated therapeutic strategies.